The Role of Scientific Integration in Contemporary Ijtihād: Researchers' Perspectives in State Islamic Universities - Maraimbang Daulay; Idris Siregar; Sayed Akhyar (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
particularly within State Islamic Higher Education Institutions (PTKIN) in Indonesia. In this context, Ijtihād, as a pivotal instrument in the development of Islamic law, can no longer rely solely on normative-textual approaches; rather, it must be contextualised through interdisciplinary and integrative perspectives. The discourse on integrating Islamic and general sciences has become increasingly critical, especially considering the emergence of ideas such as the Islamisation of knowledge and the reconstruction of Islamic epistemology. This study examines the contextualisation of Ijtihād within the knowledge integration framework at PTKIN. Employing a multisite qualitative approach based on grounded theory, fieldwork was conducted at UIN Sumatera Utara (UINSU), UIN Syahada Padangsidimpuan, and STAIN Mandailing Natal. Data collection techniques included focus group discussions, in-depth interviews, observation, and document analysis. The findings reveal that the contextualisation of Islamic law through integrated academic models continues to face structural, epistemological, and institutional challenges. UINSU applies the Wahdat al-ʿUlūm model, UIN Syahada employs a theo-anthropo-eco-centric approach, while STAIN Mandailing Natal remains embryonic. This research asserts that integrating knowledge to contextualize Islamic law demands academic culture reform, intellectual authority strengthening, and epistemological courage to transcend the dichotomy between religious and secular sciences. Thus, Ijtihād emerges not merely as a normative discourse but as an academic praxis with significant implications for transforming knowledge and advancing Islamic civilisation locally and globally. The academic contribution of this research lies in mapping the patterns of knowledge integration implemented in PTKIN and offering a critical analysis of the challenges faced in the contextualization of ijtihad. These findings enrich the discourse on contemporary Islamic legal studies by broadening the methodological horizons of ijtihad through interdisciplinary approaches